Identification of the Quadrature Resonances Using Modal Nonsynchronous Perturbation Testing and Dynamic Stiffness Approach for an Anisotropic Rotor System with Fluid Interaction - Eungu Jang; Agnes Muszynska; Young-Pil Park; Chang-Ho Kim (International Journal of Rotating Machinery)
The paper presents the dynamic analysis of an anisotropic rotor system with fluid interaction by using modal nonsynchronous perturbation testing and dynamic stiffness approaches. The anisotropic rotor system produces more complex rotor behavior than an isotropic system. In particular, the existence of the quadrature resonance phenomenon for backward precession is demonstrated. A symmetric rotor supported anisotropically by one fluid lubricated bearing and one rolling element bearing simulates rotating machinery behavior. A dynamic stiffness anisotropy algorithm which includes fluid terms is used to process experimental data in order to identify lightly loaded journal fluid film force parameters. The existence of the quadrature resonance for backward precession obtained from the experiment is compared with the analytical model. The results from modeling show strong agreement with experimental results.